Fecal Calprotectin Levels Predict Histological Healing in Ulcerative Colitis - Patel, Anish; Panchal, Hinaben; Dubinsky, Marla C. (Inflammatory bowel diseases, 2017)
Mucosal healing as measured by endoscopic activity is the therapeutic target for ulcerative colitis (UC) and associated with improved outcomes. We investigated the clinical utility of fecal calprotectin (FC) levels to predict depth of remission, including histological remission in patients with UC.MethodsWe performed a retrospective chart review of patients with UC who underwent a full colonoscopy and FC measured within 6 weeks before colonoscopy at a tertiary inflammatory bowel disease center. Clinical, endoscopic, and histological disease activity was assessed by Patient Reported Outcomes (PRO2), Mayo endoscopic score (0–3), and Nancy score (0–4), respectively. Outcomes of interest included (1) deep remission (PRO2 remission and Mayo score 0) and (2) deeper remission (deep remission plus Nancy score 0/1). Mann–Whitney U and Kruskal–Wallis tests and area under the curve–receiver operating characteristic curve analysis were used to evaluate accuracy of the predictive values.ResultsIn 68 patients, increasing FC levels were significantly associated with disease extent (P = 0.006), Mayo score (P = 0.001), and Nancy scores (P < 0.001). Patients with Mayo score 0/1 and Nancy score ≤1 (n = 20) had significantly lower FC levels compared with Mayo 0/1 and Nancy ≥ 2 (31 versus 231; P < 0.001). FC level of ≤60 μg/g predicted deep remission (area under the curve = 0.92, sensitivity 86%, and specificity 87%) and deeper remission (area under the curve = 0.91, sensitivity 83%, and specificity 90%).ConclusionsFC levels significantly correlated with endoscopic extent, mucosal healing, and histological activity, and reflect microscopic disease activity even in the face of macroscopic healing. An FC level of ≤60 μg/g robustly predicted depth of remission, suggesting that FC can be used instead of colonoscopy in a treat-to-target paradigm in patients with UC.